2015
DOI: 10.1186/s12859-015-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and CpG islands among hepatitis B virus genotypes in Europe

Abstract: BackgroundHepatitis B virus (HBV) genotypes have a distinct geographical distribution and influence disease progression and treatment outcomes. The purpose of this study was to investigate the distribution of HBV genotypes in Europe, the impact of mutation of different genotypes on HBV gene abnormalities, the features of CpG islands in each genotype and their potential role in epigenetic regulation.ResultsOf 383 HBV isolates from European patients, HBV genotypes A-G were identified, with the most frequent bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…Consistent with the previous studies (Zhang et al 2013 ; Zhong et al 2015 ; Hou et al 2015 ), CGI and split CGII were much more common in HBV genotype B compared to genotype C. Nevertheless, 30 clones in genotype C from two patients (one CHB patient and one ACLF patient) contained CGI, while among the 16 clones in genotype B from a CHB patient, only three clones contained CGI.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with the previous studies (Zhang et al 2013 ; Zhong et al 2015 ; Hou et al 2015 ), CGI and split CGII were much more common in HBV genotype B compared to genotype C. Nevertheless, 30 clones in genotype C from two patients (one CHB patient and one ACLF patient) contained CGI, while among the 16 clones in genotype B from a CHB patient, only three clones contained CGI.…”
Section: Resultssupporting
confidence: 88%
“…Although the function of CGI remains unclear, its absence might induce less methylation of the first CpG-rich region in HBV genotype C (Zhang et al 2013 ), and likely to be associated with the progressive liver diseases caused by HBV genotype C. To note, as shown in the present study, 30 clones in genotype C from two patients (one CHB patient and one ACLF patient) contained CGI, while among the 16 clones in genotype B from a CHB patient, only three clones contained CGI. Different from the previous studies (Hou et al 2015 ; Zhang et al 2013 ; Zhong et al 2015 ), data from HBV quasispecies emphasize that, distribution of CpG islands does not abide by genotypes strictly.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The absence of CpG island I is common in genotypes A, C, F, G and H, and new CpG islands are common in genotypes B, C, E, F, H, but rare in A, D, and G [ 21 , 22 ]. However, the findings of the present study showed that there were significant differences between specific subtypes, and that every subtype may possess a different CpG island distribution within the same genotype ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, six CpG islands, including three newly identified CpG islands (IV, V, and VI), are generally accepted to exist. These CpG islands are located at the transcription start site or are located upstream and downstream of the promoters [ 20 22 ]. Host DNA methyltransferase mediates CpG methylation, and methylated HBV CpG islands limit their regulation of viral protein expression [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%